Respiratory Distress and Its Outcome among Neonates Admitted to Neonatal Intensive Care Unit of Mukalla Maternity and Child Hospital, Yemen - Awad Bahwal , Saleh; Ahmed Jawass, Mazin; Salim Bahartha , Ali (Diyala Journal of Medicine, 2020)
Background: Respiratory distress is one of the most common causes of admission in neonatal intensive care unit . Objective: To determine the causes and to study the various risk factors associated with development of respiratory distress and outcomes of respiratory distress in neonates admitted to neonatal care unit of Mukalla Maternity and Child Hospital in Al- Mukalla city, Hadhramaut Governorate, Yemen. Patients and Methods: This is a prospective study covering the 12-month period between April 2018 to March 2019 to neonates admitted to neonatal care unit of Mukalla MaternityandChild hospital. Results: A total of 430 patients were admitted to the neonatal care unit. Number of cases presented with respiratory distress was 250, representing 58.1% of all cases admitted. The most frequent underlying cause for respiratory distress in children was respiratory distress syndrome (44%), followed by transient tachypnea of the newborn (18.8%), birth asphyxia (14%), meconium aspiration syndrome (12%), and other causes (11.2) (CHD 10(4%), sepsis (3.2%), congenital pneumonia (2.4%), and congenital anomalies (1. 6%). The majority of cases of respiratory distress syndrome and transient tachypnea of newborn were males with statistical significant difference. The outcome of neonatal respiratory disorders was: cure in 40.4% of cases, patients discharged with complications in 10.4 % of cases, and death in 49.2% of cases. The highest case fatality rate of neonatal respiratory distress diseases were respiratory distress syndrome (81.8%) followed by meconium aspiration syndrome (56.7% ) and birth asphyxia (34.3% ). Conclusion: Respiratory distress syndrome was the main cause of respiratory distress followed by transient tachypnea of newborn.